Analisis Keandalan Sistem Distribusi 20kV Pada Penyulang Pujon PT. PLN (PERSERO) ULP Batu - Wijaya Kusuma; Ruwah Joto; Mochammad Mieftah; Awan Setiawan (Politeknik Negeri Malang, 2022)
At PT. PLN (Persero) ULP Batu, Pujon feeder is one of the 9 feeders in the distribution system that supplies several areas in PT. PLN (Persero) ULP Batu. At the Pujon feeder, the number of disturbances that occurred from January to November 2021 occurred twenty-two times, with details of eighteen temporary disturbances and four permanent disturbances. The number of disturbances that often occur can affect the feeder who is working normally. This can cause voltage drops and power losses, causing the flow of electric power to be less than optimal and detrimental to customers or consumers. Because it requires maneuvering so that the disturbance does not spread to all feeders and cause one feeder to experience a blackout. Based on the problems that occur, maneuver analysis is needed to reduce the impact of disturbances on the Pujon feeder and to maintain the reliability value of the distribution system at PT. PLN (Persero) ULP BATU.